UPAYA PENINGKATAN PENGETAHUAN PENGGUNAAN BIOFERTILIZER DI KELOMPOK USAHA TANI DUSUN GAPUK DESA TEBING TINGGI PANGKATAN KECAMATAN PANGKATAN KABUPATEN LABUHANBATU - Hilwa Walida, Fitra Syawal Harahap, Ibnu Rasyid Munthe, Sarifuddin (JURNAL BIMA, 2024)
One of the farming business groups located in Gapuk Hamlet, Tebing Tinggi Pangkatan Village is a chili cultivator who started his chili farming business in 2018. Chilli cultivation is carried out on an area of 2,800 m2 with a production of 1.5 tons and a total profit of 50 million rupiah during 1 plant life cycle. However, based on the survey results, it is known that the use of chemical fertilizers in the cultivation of chili farming is very large and wasteful, so it can cause many negative impacts, one of which is Fusarium attacks. This activity aims to provide knowledge about the impact of excessive use of chemical fertilizers and chemical pesticides and the benefits of biofertilizers. Efforts to increase knowledge are carried out by providing socialization and interspersed with giving pretests and posttests. The pretest and posttest each contain 10 questions, then the results are calculated using a paired t-test. The results showed significant differences in the two socialization materials, indicating that there were differences in knowledge before and after being given the socialization materials. The paired t-test result for the first material was 0.002837 and the second material was 0.00319. Based on this, it can be said that providing socialization can increase the knowledge of farming business groups in Gapuk Tebing Tinggi Pangkatan Hamlet, Pangkatan District, Labuhanbatu Regency.